Implementation of Medication Therapy Management (MTM) in Community Pharmacies - Buresh, Megan (The University of Arizona., 2008)
Class of 2008 Abstract === Objectives: The purpose of this study was to identify how community pharmacies have integrated medication therapy management (MTM) programs into their workflow and specifically determine the changes that were made in order to deliver such services. Methods: This was a descriptive study on the implementation of MTM programs in community pharmacies. Pharmacy managers associated with Cardinal Health, Medicine Shoppe International, United Drugs, the Iowa Pharmacy Association (IPA) and 10 additional selected pharmacists were invited to take an online survey regarding MTM program implementation in their pharmacy. Exclusion criteria were those pharmacists that did not provide any MTM services from January 2006 through December 2007. The primary dependent variables included time spent training, time to complete clinical pharmacy program sessions, scheduling and implementing clinical pharmacy sessions, staffing, and cost for additional equipment. Data analysis included percents and frequencies for categorical variables addressed in the internet survey. Results: Pharmacists that participated in this survey were mostly male (82%) and had been practicing for greater than 10 years. Only 3 out of 17 participants were female and all were a part of the group practicing for less than 10 years. The majority of participants in both groups completed 0-2 MTM sessions per week (p=0.65). In order to complete these sessions, the hiring of additional staff was not required (82%) nor was the purchase of additional equipment (70%). Conclusions: The implementation of MTM programs in community pharmacies requires little to no additional time or money. With this data, more pharmacists should be inclined to provide MTM sessions.